Final Year Project Supervisor Acceptance System (FYPSA) / Muhammad Fikri Mohd Firdaus and Ros Syamsul Hamid - Mohd Firdaus, Muhammad Fikri; Hamid, Ros Syamsul (College of Computing, Informatics and Media, UiTM Perlis, 2023)
A majority of the final year students in Universiti Teknologi Mara Cawangan Perlis faced with unpleasant issue due to finding the suitable supervisor to finish their final year project. The Final Year Project Supervisor Acceptance System (FYPSA) which is an application that can bring together the student and supervisor by helping them on searching for supervisor, submitting, reviewing, and accepting the final year project request. The goal of this project is making FYPSA based on mobile application for android user to improve the communication between students and supervisor to completing the first phase of final year project which is proposing the project title that usually do manually. The development of FYPSA application used the System Development Life Cycle (SDLC) by implementing the agile model as the methodology. A user acceptance testing was conducted with 30 respondents who are the students in Universiti Teknologi Mara Cawangan Perlis to determine theusability and functionality of the FYPSA by evaluating the questionnaires that were divided into two categories respectively. Results of the system evaluation showed that most of the participant were satisfied with all categories provided. Therefore, FYPSA can assist the student and the supervisor to complete the first phase of final year project run smoothly without taking a lot of time to find and approve the project proposal.